Severe Atopic Dermatitis In Spain: A Real-Life Observational Study - Sicras-Mainar A; Navarro-Artieda R; Armario-Hita JC (Dove Medical Press, 2019)
Antoni Sicras-Mainar,1 Ruth Navarro-Artieda,2 José C Armario-Hita3 1Scientific Direction, Real Life Data, Madrid, Spain; 2Medical Documentation, Germans Trias i Pujol Hospital, Barcelona, Spain; 3Dermatology Service, Puerto Real University Hospital, Cadiz University, Cádiz, SpainCorrespondence: Antoni Sicras-MainarScientific Direction, Real Life Data, c/Cronos, 24–26, P3 - Bajo E36, Madrid 08037, SpainTel +34 91 007 15 92Email antoni.sicras@rlifedata.comObjective: To determine the epidemiology and characterize the treatment prescribed for severe atopic dermatitis (AD) in children/adults in usual clinical practice.Methods: Observational, retrospective study made through review of medical records of Spanish patients aged ≥6 years. Patients diagnosed with severe AD who required care between 2013 and 2017 were included. The study groups were: 6–12 years; 13–18 years; and > 18 years. Patients were followed for 5 years. The main measurements were the prevalence of AD, comorbidity and treatment duration. Statistical significance was established as p <0.05.Results: We included 2323 patients with severe AD. The overall prevalence was 0.10% (95% CI: 0.09–0.11%) and was 0.39%, 0.23% and 0.07% in the 6–12 years, 13–18 years and >18 years age groups, respectively (p <0.001), the percentage of males was 58%, 48.6% and 39%, respectively, and general comorbidity was 0.1, 0.2 and 0.9 points, respectively (p <0.001).The most frequent comorbidities were asthma in 49.0%, 44.9% and 20.8%, respectively (p <0.001), and anxiety in 79.7%, 65.8% and 67.3%, respectively (p <0.001). Oral corticosteroids were administered in 97.3%, 90.9% and 81.7%, respectively (concomitant-medication). Cyclosporine (45.3%), azathioprine (15.9%) and methotrexate (9.0%) were the most frequently prescribed drugs; biologic agents were administered in 5.8% of patients (for AD).Conclusion: In AD the presence of comorbidities was significant, especially in the psychological, immunoallergic and cardiovascular areas. Cyclosporine was the most widely used immunosuppressant. There was a degree of variability in the use and duration of the treatments prescribed.Keywords: severe atopic dermatitis, epidemiology, comorbidity, treatment, immunosuppressants, biologics